ECOLOGICAL-FAUNIST ANALYSIS OF COXINALLIDES (COLEOPTERA, COCCINELLIDAE) OF THE KARSHI OAKH (Spectrum Journal of Innovation, Reforms and Development, 2022)
Entomological material was collected for the study of coccinellides (Coleoptera, Coccinellidae) of the Karshi oasis in 2018-2021. Analysis of the material revealed the distribution of 8 types of coccinellides.